Spatial limitation of jurisdiction in administrative proceedings - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The competence of administrative bodies is an important precondition for the lawful conducting of administrative proceedings. About this kind of competence must be taken care ex officio during the entire procedure, and violations of rules on competence represents a significant violation of the rules in administrative procedure. Among the numerous novelties introduced in the administrative procedure by the Law on General Administrative Procedure from 2016 there are certain changes in rules on determining the competence of the body conducting the administrative procedure. The new rules on the competence of bodies in administrative procedure, and especially on the spatial limitation of competence, cannot be assessed as a significant improvement of the legal regime of administrative procedure, given that some of them represent a significant limiting factor for effective and economical management of administrative procedures. The future legislative revision of the administrative procedure should therefore be used to regulate, above all, issues of legal aid between administrative bodies, as well as administrative bodies and courts, and in particular the rules on spatial limitation of jurisdiction, which would enable the administrative body to, in case of urgency, take official action on territory of another body, with the duty to inform the authority in charged with territory where the action was taken. Careful and fundamental amendments to the legal provisions on the competence of administrative bodies would provide the necessary legal preconditions for efficient and economical conducting of administrative proceedings, and the rights and legal interests of the parties, as well as their legal security, would no longer be denied.